Study on microdroplet diameter enlargement for enhancement of moisture separation efficiency - Yoshihiro ISHIKAWA (The Japan Society of Mechanical Engineers, 2017)
Wave-shaped vanes are widely used in various power and energy systems for improved efficiency and prevention of droplet erosion. The vanes consist of wave-shaped parallel plates with pockets. As wet steam flows through the wave-shaped path, heavier droplets are thrown to the outside and captured in the pockets while frequently changing direction. However, microscale droplets are difficult to completely catch since they flow straight with the steam and are carried over through the wave-shaped vanes. Accordingly, we previously investigated installing a wire mesh at the inlet of the wave-shaped vanes to enhance the droplet capture efficiency by enlarging the microdroplets. In the present study, we examined the effect of the wire mesh configuration on enlarging the microdroplet size through air-water experiments. Droplet diameters were measured by a real-time image processing system consisting of a CCD camera and pulsed laser light source. The results showed that the droplet diameter distribution largely depended on the wire mesh configuration. We evaluated the mass flow ratio for droplets with a diameter smaller than the threshold diameter. The ratio was smallest in the case of the six-layer configuration of 0.65 mm diameter compared with two other cases, 0.19 and 0.80 mm, whereas the pressure loss was largest in the case of 0.19 mm. We conducted flow visualization at the outlet of the wire mesh using a high-speed camera. The visualization results showed that a liquid film had formed over the layered wire mesh and the surface wave of the liquid film on the last layer induced the detachment of enlarged droplets from the liquid film.